Biopolymer films based on chitosan/potato protein/linseed oil/ZnO NPs to maintain the storage quality of raw meat. (1st December 2020) - Wang, Chenjie; Chang, Tong; Dong, Shuang; Zhang, Dongliang; Ma, Chengye; Chen, Shanfeng; Li, Hongjun
Highlights: Transparency and tensile strength of films were improved by ZnO NPs. Fcpzl exhibited excellent moisture barrier capability. ZnO NPs could improve the surface morphology of the film. Intramolecular and intermolecular interactions occurred in the film. Fcpzl possessed the best protective effect of raw meat. Abstract: Biopolymer films based on chitosan/potato protein/linseed oil/ZnO NPs were developed to maintain the storage quality of raw meat. Results indicated that the incorporation of ZnO NPs could effectively improve the transparency and tensile strength of the films, while addition of linseed oil could make the composite film maintain good elastic property. Films blended with chitosan/potato protein/linseed oil/ZnO NPs (Fcpzl) exhibited an excellent moisture barrier capability. SEM showed that ZnO NPs could harmoniously exist in various polymers matrix. FTIR analysis demonstrated that different components were bound together by intramolecular and intermolecular interactions, among which hydrogen bonds were the main force. Raw meat samples were wrapped with different films to evaluate the preservative effect during 4 °C storage. Results indicated that Fcpzl possessed best protective effect of raw meat with excellent acceptable sensory properties during 7 days storage, which could reduce the speed of increasing pH and total bacterial counts.